Pengaruh Stres Kerja, Efikasi Diri dan Kreatifitas Terhadap Kinerja Pegawai Badan Layanan Umum Daerah Rumah Sakit Umum Daerah Djasamen Saragih Pematangsiantar - Sarjani Saragih; Elisabet Siahaan (Universitas Malikussaleh, 2021)
The purpose of this research is to identify and analyze the influence of job work stress, self-efficacy, and creativity on the employee’s performance of the Regional Public Service Agency at RSUD Djasamen Saragih Pematangsiantar. This research is explanatory, namely research that aims to explain the relationship between variables that have been determined as variables to be studied. The data used in this study are primary data and secondary data. The data analysis method used is quantitative descriptive using multiple linear regression. The population in this research was 72 employees. The number of samples in this research was 72 employees with saturated sampling data collection techniques. The result showed that work stress, self-efficacy, and creativity significantly affect the performance of BLUD employees at RSUD Djasamen Saragih Pematangsiantar. The partial test showed that self-efficacy and creativity variable has positive and significant on employee performance of BLUD employees at RSUD Djasamen Saragih Pematangsiantar. In contrast, the work stress variable has negative and significant on employee performance. BLUD employees at RSUD Djasamen Saragih Pematangsiantar. Creativity is a dominant variable influencing employee performance at RSUD Djasamen Saragih Pematangsiantar